2018
DOI: 10.1111/jog.13687
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal complications in pregnant women with urinary tract infection caused by Escherichia coli

Abstract: According to this study in a Mexican population, the number one admission diagnosis in women with UTI due to E. coli was threatened preterm labor, and fever and threatened abortion. E. coli was sensitive to more than 90% of piperacillin-tazobactam, amikacin, nitrofurantoin and carbapenems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
0
17
1
4
Order By: Relevance
“…25 A study in Mexico showed that Eschericia coli was identified as a major cause of the threat of preterm labor with the majority of subjects eventually experiencing preterm labor. 26 Regarding cytokines, amniotic fluid cytokines such as interleukin-1 (IL-1), interleukin-6 (IL-6), interleukin-8 (IL-8), tumor necrosis factor-alpha (TNF-α), and granulocyte colony stimulating factor (G-CSF) is strongly associated with infection, premature rupture of membranes and preterm labor which cannot be stopped with tocolytic therapy. The cytokines together with prostaglandins will stimulate premature labor.…”
Section: Discussionmentioning
confidence: 99%
“…25 A study in Mexico showed that Eschericia coli was identified as a major cause of the threat of preterm labor with the majority of subjects eventually experiencing preterm labor. 26 Regarding cytokines, amniotic fluid cytokines such as interleukin-1 (IL-1), interleukin-6 (IL-6), interleukin-8 (IL-8), tumor necrosis factor-alpha (TNF-α), and granulocyte colony stimulating factor (G-CSF) is strongly associated with infection, premature rupture of membranes and preterm labor which cannot be stopped with tocolytic therapy. The cytokines together with prostaglandins will stimulate premature labor.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation could be related to infectious or non-infectious causes, and the resulting signaling is deleterious for pregnancy and is associated with poor fetal outcomes, such as premature rupture of membranes and preterm birth (Tchirikov et al , 2018). A great deal of evidence supports that Escherichia coli is one of the most common Gram-negative bacteria causing urinary tract infections during pregnancy, which in turn may result in preterm labor (Dautt-Leyva et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract infections (UTIs) are relatively common bacterial infections during pregnancy. UTIs, especially acute pyelonephritis, could pose significant maternal (medical and obstetric) and neonatal complications, including threatened abortion, preterm labour, neonatal mortality, etc . Clearly, administration of safe antibiotics to pregnant women with UTIs is a frequent practice.…”
Section: Introductionmentioning
confidence: 99%
“…UTIs, especially acute pyelonephritis, could pose significant maternal (medical and obstetric) and neonatal complications, including threatened abortion, preterm labour, neonatal mortality, etc. 1 Clearly, administration of safe antibiotics to pregnant women with UTIs is a frequent practice. A recent report from the US found that 7.2% of pregnant women had a diagnosis of UTI.…”
Section: Introductionmentioning
confidence: 99%